2017
DOI: 10.1038/srep40821
|View full text |Cite
|
Sign up to set email alerts
|

Crotalus atrox venom preconditioning increases plasma fibrinogen and reduces perioperative hemorrhage in a rat model of surgical brain injury

Abstract: Perioperative bleeding is a potentially devastating complication in neurosurgical patients, and plasma fibrinogen concentration has been identified as a potential modifiable risk factor for perioperative bleeding. The aim of this study was to evaluate preconditioning with Crotalus atrox venom (Cv-PC) as potential preventive therapy for reducing perioperative hemorrhage in the rodent model of surgical brain injury (SBI). C. atrox venom contains snake venom metalloproteinases that cleave fibrinogen into fibrin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, some snake venoms contain both pro‐coagulant and anti‐coagulant proteins. We previously demonstrated that whole C. atrox venom reduces perioperative hemorrhage in a rat model of surgical brain injury (Kim et al, ). Therefore, we hypothesized that there would be a protein(s) which could be harnessed for therapeutic benefit to protect against hemorrhagic transformation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, some snake venoms contain both pro‐coagulant and anti‐coagulant proteins. We previously demonstrated that whole C. atrox venom reduces perioperative hemorrhage in a rat model of surgical brain injury (Kim et al, ). Therefore, we hypothesized that there would be a protein(s) which could be harnessed for therapeutic benefit to protect against hemorrhagic transformation.…”
Section: Discussionmentioning
confidence: 98%
“…Each analyzed fraction was reduced with dithiothreitol and alkylated with iodoacetamide (Kim et al, ). Proteins were digested with proteomics‐grade porcine pancreatic trypsin (Sigma–Aldrich) and then desalted (C18 ZipTips, EMD Millipore, Billerica, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Hemorrhage is a critical issue in neurosurgery and is implicated in contributing to SBI [9,44]. Firstly, intraoperative bleeding causes local ischemic insult and systemically plagues the cardiovascular system.…”
Section: Pathophysiology Of Surgical Brain Injurymentioning
confidence: 99%
“…In the following sections, we expand on the concept of preconditioning and propose the use of venom-derived proteins as a preconditioning therapy for SBI. [35,44,45,67,68], it has often been noted that clinical translation is limited since many injuries occur spontaneously. In the last few decades, the potential of PC, especially for scheduled (or elective) surgeries, has become a real focus in hopes of developing an effective therapy.…”
Section: Neurotherapeutics and Preconditioning In Surgical Brain Injurymentioning
confidence: 99%
See 1 more Smart Citation